THE ROLE OF HUMAN FACTOR IN THE DEVELOPMENT OF AGRICULTURE IN MONTENEGRO - Božović, Žarko; Đurašković, Jovan (Economics of Agriculture, 2014)
We have started from the analysis of existing human resources in the paper, from the point of view of regional, qualification and age structure of the active labour force. Basic research method is deduction method, because we start from the general towards special and individual, with the aim to bring human factor and development of agriculture in Montenegro into connection. With regards to the key role of the human factor in the development of agriculture, a question emerges: is this factor in Montenegro a real opportunity or a constraint? Upon having insight into the existing situation of the human factor, we can conclude that there is an obvious discrepancy between demographic and economic centres. Expressed migration of the population from the north towards the south and from villages to cities brought the development of agricultural production into question. When the human factor engaged in agriculture is concerned, old population and elderly households prevail, which is a serious threat to the development, because depopulation and "salinization" caused abandoning villages, deagrarization and space devastation.